2022
DOI: 10.1111/and.14475
|View full text |Cite
|
Sign up to set email alerts
|

Silymarin modulates cadmium‐induced oxidative stress in human spermatozoa

Abstract: Environmental pollutants such as cadmium can negatively affect sperm parameters and decrease male fertility by inducing oxidative stress. Antioxidants are considered a useful strategy for oxidative stress conditions to neutralize free radicals and strengthen the antioxidant defence system. In this study, the effects of the common application of silymarin, as a natural antioxidant, with cadmium were assessed on human sperm. The washed human sperm samples were divided into five groups:(1) spermatozoa at 0-hour; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Given that a reduction in antioxidant defense mechanisms is associated with a decrease in semen quality [56,57], it is possible to infer that the favorable antioxidant effects of propolis may support its ability to improve semen quality when reproductive toxicity is induced. Malonyl dialdehyde (MDA), which is a stable end product created from peroxidation of essential (i.e., polyunsaturated) fatty acids in the cell [58], is considered a marker of increased cellular oxidation reactions beyond the capacity of antioxidant defense mechanisms, a state termed oxidative stress [59][60][61][62]. Among 12 mechanistic studies, five have revealed a reduction in testicular MDA when propolis is present amid induced toxicity conditions (Table 2).…”
Section: Mechanisms Of Action Of Propolis In Ameliorating Reproductiv...mentioning
confidence: 99%
See 1 more Smart Citation
“…Given that a reduction in antioxidant defense mechanisms is associated with a decrease in semen quality [56,57], it is possible to infer that the favorable antioxidant effects of propolis may support its ability to improve semen quality when reproductive toxicity is induced. Malonyl dialdehyde (MDA), which is a stable end product created from peroxidation of essential (i.e., polyunsaturated) fatty acids in the cell [58], is considered a marker of increased cellular oxidation reactions beyond the capacity of antioxidant defense mechanisms, a state termed oxidative stress [59][60][61][62]. Among 12 mechanistic studies, five have revealed a reduction in testicular MDA when propolis is present amid induced toxicity conditions (Table 2).…”
Section: Mechanisms Of Action Of Propolis In Ameliorating Reproductiv...mentioning
confidence: 99%
“…Malonyl dialdehyde (MDA), which is a stable end product created from peroxidation of essential (i.e., polyunsaturated) fatty acids in the cell [ 58 ], is considered a marker of increased cellular oxidation reactions beyond the capacity of antioxidant defense mechanisms, a state termed oxidative stress [ 59 - 62 ]. Among 12 mechanistic studies, five have revealed a reduction in testicular MDA when propolis is present amid induced toxicity conditions ( Table 2 ).…”
Section: Mechanisms Of Action Of Propolis In Ameliorating Reproductiv...mentioning
confidence: 99%